Integrated Lymphopenia Analysis in Younger and Older Patients With Multiple Sclerosis Treated With Cladribine Tablets - Giovannoni, Gavin; Coyle, Patricia K.; Vermersch, Patrick; Walker, Bryan; Aldridge, Julie; Nolting, Axel; Galazka, Andrew; Lemieux, Caroline; Leist, Thomas P. (Frontiers in Immunology, 2021)
Cladribine tablets (CladT) preferentially reduce B and T lymphocyte levels. As aging is associated with a decline in immune function, the effect of CladT on lymphocyte levels may differ by age. This post hoc analysis combined data from the Phase 3 CLARITY, CLARITY Extension, and ORACLE-MS studies to examine the effect of age (≤50 or >50 years) on lymphopenia following CladT 3.5 mg/kg (CladT3.5; cumulative dose over 2 years) treatment over 96 weeks. Both CladT3.5 and placebo were given over Weeks 1 and 5 (Year 1 treatment) and Weeks 48 and 52 (Year 2 treatment) from the start of the studies. Absolute lymphocyte count (ALC) and levels of lymphocyte subsets were examined in 1564 patients (Age ≤50 [placebo: N=566; CladT3.5: N=813]; Age >50 [placebo: N=75; CladT3.5: N=110]). In both age groups, following CladT3.5 treatment, nadir for ALC occurred at Week 9 (8 weeks following start of Year 1 treatment) and Week 55 (7 weeks following start of Year 2 treatment) of the 96-week period; for CD19+ B lymphocytes, nadir occurred at Week 9 (Year 1) and Week 52 (Year 2). For CD4+ T lymphocytes, nadir occurred at Week 16 (Year 1) in both age groups, and at Weeks 60 and 72 (Year 2) in the Age ≤50 and >50 groups, respectively. Nadir for CD8+ T lymphocytes occurred at Week 16 (Year 1) and Week 72 (Year 2) in the Age ≤50 group and levels remained in the normal range; nadir occurred at Week 9 (Year 1) and Week 96 (Year 2) in the Age >50 group. Lymphocyte recovery began soon after nadir following CladT3.5 treatment and median levels reached normal range by end of the treatment year in both age groups. By Week 96, ~25% of patients treated with CladT3.5 reported ≥1 episode of Grade ≥3 lymphopenia (Gr≥3L). The rate of certain infections was numerically higher in older versus younger patients who experienced Gr≥3L. In conclusion, CladT3.5 had a similar effect on ALC and lymphocyte subsets in both younger and older patient groups.